2017
DOI: 10.1017/s0033291717001763
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular fitness in late adolescent males and later risk of serious non-affective mental disorders: a prospective, population-based study

Abstract: Lower fitness in late adolescent males is associated with increased risk of serious non-affective mental disorders in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…As shown in Tables and , 38 studies met criteria for inclusion in the qualitative synthesis and all were published after 2005 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Tables and , 38 studies met criteria for inclusion in the qualitative synthesis and all were published after 2005 .…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the cross‐sectional studies included a total of 2698 cases (across Stages 1–4) and 3129 HC and all except one of these studies comprised 55–100% males. The median sample age was about 33 years, and 13 studies reported the inclusion of affective or schizoaffective alongside non‐affective psychoses .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…xi Supplemental Seven citations reported rates deriving from the army, army conscripts or army veterans [39][40][41][42][43][44][45] . These studies are summarised in Table 6 below.…”
Section: Incidence Of Psychotic Disorders In Special Population Groupsmentioning
confidence: 99%
“…One citation reported the effects of frequent cannabis use on risk of developing nonaffective disorders (OR: 2.0, 95%CI: 0.8-4.7), schizophrenia (OR: 3.7, 95%CI: 2.3-5.8) and brief psychosis (OR: 2.2, 95%CI: 1.0-4.7) 41 . Two further citations examined the effects of resting heart rate on schizophrenia (HR for resting heart rate of >82 beats per minute: 1.10 (95%CI: 1.08-1.12) and bipolar disorder (OR: 1.01, 85%CI: 1.00-1.03) 42 and the effects of cardiovascular fitness on nonaffective (HR for low fitness: 1.44, 95%CI:1.29-1.61) and other psychotic disorders (HR: 1.41, 95%CI: 1.27-1.56) 44 . A final citation found an incidence of non-affective disorders of 11 per 100,000 personyears and of schizophrenia of 3 among English army personnel 43 .…”
Section: Incidence Of Psychotic Disorders In Special Population Groupsmentioning
confidence: 99%